FEASABILITY,IMPLEMENTATION AND EVALUATION OF THE DEVELOPMENT OF ACCOUNTING LEARNING THROUGH THE ADDIE MODEL WITH MEDIA AND INTRODUCING TO ACCOUNTING TEXTBOOKS - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study was conducted to: 1) conduct a feasability test for developing accounting learning through media and accounting teaching materials. 2) implement or implement a model in accounting learning in class.